Development of Interactive Multimedia Based on Gamification Learning to Improve Learning Outcomes for Children with Disabilities - Zefanya Sherafim; I Kadek Suartama; Dewa Gede Agus Putra Prabawa (LPPPI Publishing, 2026)
This research and development aims to produce a gamification-based interactive multimedia called